Hubungan Perilaku Penggunaan APD, Status Vaksinasi, Zona Kerja Dengan Status Covid-19 Pada Tenaga Kesehatan Di Rumah Sakit Pertamina Bintang Amin - Neno Fitriyani Hasbie; Vera Yulyani; Dessy Hermawan; Fauzurrahman Al Amin (Universitas Malahayati Lampung, 2022)
ABSTRACT If a person has been infected with the Coronavirus and received a full COVID-19 vaccination, which is up to 2 doses of the vaccine, his body can quickly form strong antibodies to fight the virus and prevent serious complications when he is later exposed. The effectiveness of the COVID vaccination is known to reduce the symptoms experienced when exposed to the COVID-19 virus. Especially for health workers as the front line in breaking the chain of the current COVID-19 pandemic. Instead, this study was conducted to find out the related factors that can affect the status of COVID. Observational analysis using a cross-sectional method approach using a proportion estimation formula for a total of 145 samples. Data collection began in November 2021. This research was conducted at Pertamina Bintang Amin Hospital in Bandar Lampung. Statistical data chi-square test using SPSS 25. The research respondents totaled 145 health workers, it was found that the most health workers with good PPE use behavior with unconfirmed were 61 respondents (77.2%) and the least was bad use behavior with confirmed status 17 respondents (25.8%). Meanwhile, the vaccination status and the booster dose COVID status were obtained. The booster dose vaccination status has been vaccinated and not confirmed, there are 89 respondents (82.4%). And the non-COVID work zone with confirmed COVID status obtained 102 respondents (76.7%). There is no relationship between the behavior of using PPE with COVID status having a p-value of 0.509 with Odds Ratio (OR) = 0.705, there is a relationship between vaccination status and COVID status having a p-value of 0.002 with Odds Ratio (OR) = 0.280, and there is no relationship The work zone with COVID status has a p-value of 0.437 with Odds Ratio (OR) = 0.608. There is no relationship between PPE use behavior, work zone, and COVID-19 status. There is a relationship between vaccination status and COVID-19 status in Pertamina Bintang Amin Hospital Health Workers 2021. Key words: PPE Use Behavior, COVID Status, Vaccination Status, and Work Zone ABSTRAK Bila seseorang sudah pernah terinfeksi virus Corona dan menerima vaksinasi COVID-19 secara penuh, yaitu sampai 2 dosis vaksin, tubuhnya bisa dengan cepat membentuk antibodi yang kuat untuk melawan virus tersebut dan mencegah komplikasi serius ketika nanti ia terpapar. Efektifitas vaksinasi COVID diketahui dapat mengurangi gejala-gejala yang dialami apabila terpapar virus COVID-19. Terutama pada tenaga kesehatan sebagai garda terdepan dalam pemutusan rantai pandemic COVID-19 saat ini. Penelitian ini dilakukan untuk mengetahu factor faktor terkait yang dapat mempengaruhi status COVID. Analitik observasional dengan menggunakan pendekatan metode cross sectional menggunakan rumus estimasi proporsi sebanyak 145 sampel keseluruhan. Pengambilan data dimulai pada bulan November 2021. Penelitian ini dilakukan di Rumah Sakit Pertamina Bintang Amin Bandar Lampung. Data statistik uji chi-square menggunakan SPSS 25. Didapatkan responden penelitian berjumlah 145 tenaga kesehatan ditemukan paling banyak Tenaga kesehatan dengan Perilaku penggunaan APD yang baik dengan tidak terkonfirmasi ialah 61 responden (77,2%) dan paling sedikit pada perilaku penggunaan buruk dengan status terkonfirmasi 17 responden (25,8%). Sedangkan pada status vaksinasi dan status COVID dosis booster didaptkan Status vaksinasi dosis booster sudah divaksin dan tidak terkonfirmasi didapatkan 89 responden (82,4%). Dan Zona kerja non-COVID dengan status COVID terkonfirmasi didapatkan 102 responden (76,7%). Tidak terdapat hubungan perilaku penggunaan APD dengan status COVID memiliki p-value sebesar 0,509 dengan Odds Ratio (OR)= 0,705, terdapat hubungan status vaksinasi dengan status COVID memiliki p-value sebesar 0,002 dengan Odds Ratio (OR)= 0,280, dan tidak terdapat hubungan Zona kerja dengan status COVID memiliki p-value sebesar 0,437 dengan Odds Ratio (OR)= 0,608. Tidak terdapat hubungan antara Perilaku Penggunaan APD, zona kerja dengan status COVID-19. Terdapat hubungan anatara status vaksinasi dan status COVID-19 pada Tenaga Kesehatan Rumah Sakit Pertamina Bintang Amin 2021. Key words: Perilaku Penggunaan APD, Status COVID, Status Vaksinasi, Zona Kerja